Signet Ring Cell Carcinoma of the Extrahepatic Bile Duct Diagnosed by Preoperative Biopsy: A Case Report - Emiri Kita; Akiko Tsujimoto; Kazuyoshi Nakamura; Kentaro Sudo; Taro Hara; Osamu Kainuma; Hiroshi Yamamoto; Makiko Itami; Taketo Yamaguchi (Case Reports in Gastroenterology, 2014)
A 73-year-old woman was admitted because of obstructive jaundice. Computed tomography revealed a stricture in the lower bile duct with enhanced bile duct wall. Endoscopic retrograde cholangiopancreatography (ERCP) revealed a tapering stenosis at the lower bile duct. Transpapillary histological biopsy using biopsy forceps through ERCP was performed; the diagnosis of signet ring cell carcinoma (SRCC) of the bile duct was established. Regional lymph node enlargement and distant metastases were not detected on diagnostic imaging. Pancreaticoduodenectomy with pylorus preservation was performed. Histological examination of the resected specimen confirmed SRCC of the extrahepatic bile duct coexisting with adenocarcinoma (ADC) of the extrahepatic bile duct with negative resection margins. However, tumor cells directly invaded the pancreatic parenchyma and the muscle layer of the duodenum, prompting us to administer adjuvant chemotherapy to the patient, with no sign of tumor recurrence at 1-year follow-up. Almost all tumors originating from the extrahepatic bile duct are ADC and other histological variants are rare. Of these, SRCC is extremely rare and only four cases have been reported. Furthermore, to the best of our knowledge, this is the first case report regarding the preoperative diagnosis of SRCC of the bile duct. Current reports indicate that younger age and Asian ethnicity are the clinical features of SRCC of the extrahepatic bile duct. Immunohistochemical staining of CK7, CK20 and MUC2 may be useful for predicting prognosis. Chemotherapy has not resulted in increased survival rates and only surgical resection currently serves as a curative treatment.